Advancing Pharmaceutical Manufacturing with Digital Twin Simulations: Benefits and Challenges - Naik, Pawan I.; Chavan, Vasant Y.; Patil, Swapnil R.; Patil, Bhupendra R.; Chaudhari, Dr. Pankaj M. (Asian Journal of Pharmaceutical Research and Development, 2025)
To make the manufacturing sector more intelligent and flexible. DTs are virtual representations of real-world systems that replicate their dynamics and behavior. Physical and virtual components, as well as information exchanges between them, make up a fully-fledged DT. Integrated DTs are used in many different product and process industries. There hasn't been a complete implementation of DT in pharmaceutical manufacturing, despite the pharmaceutical industry's recent adoption of Quality-by-Design (QbD) programs and its current digital transformation to embrace Industry 4.0. Examining the pharmaceutical industry's success in applying DT solutions is therefore crucial. Giving a summary of the state of DT development and its use in the production of pharmaceuticals and biopharmaceuticals is the goal of this narrative literature review. The latest advancements in Process Analytical Technology (PAT), data integration research, and process modeling techniques are examined. There is also discussion of the difficulties and prospects for further study in this area.